Mythological Consciousness as a Form of Social Consciousness - Malakhov, Valery; Sigalov, Konstantin; Lanovaya, Galina (Տիգրան Մեծ)
The main purpose of the article is to explain the actual role of mythological consciousness in the mod-ern spiritual life of society, thereby overcoming the generally sceptical, if not negative, attitude towards mythologisation in modern social science.The subject of the article is nature and forms of mythological consciousness. The authors‟ premise is that rather than being a collection of myths, mythological consciousness is an independent way of spiritual penetration into the world, the transformation of the sensually perceivable and the sign-symbolical reality into an inseparable whole. Mythological consciousness is interpreted as an immanent component of social consciousness. A special role is assigned to the centres of mythological consciousness, in which its nature is encoded. Mythologemes, archetypes and mentality are kindsof a link between social consciousness and social unconsciousness.By revealing the mythological nature of ideas, values, images, symbols, and signs as unavoidable forms through which worldview mindsets andconceptual pillars of modern science are formed, we find ways to unleash their true intellectual and spiritual potential. The final result of the article is the validity of the statement that the ideological structure of modern social thought is its mythological component.
Keywords: Philosophy